2016
DOI: 10.1063/1.4971970
|View full text |Cite
|
Sign up to set email alerts
|

Thermal fluctuation analysis of singly optically trapped spheres in hollow photonic crystal cavities

Abstract: We report on the behaviour of singly optically trapped nanospheres inside a hollow, resonant photonic crystal cavity and measure experimentally the trapping constant using back-focal plane interferometry. We observe two trapping regimes arising from the back-action effect on the motion of the nanosphere in the optical cavity. The specific force profiles from these trapping regimes is measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Moreover, a trapping potential depth in this work as large as 1.15 × 10 5 k B T mW −1 is obtained. Threshold power of only 0.087 μW is required for stable trapping, which is significantly decreased compared to previous PC cavity designs [39][40][41]53].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, a trapping potential depth in this work as large as 1.15 × 10 5 k B T mW −1 is obtained. Threshold power of only 0.087 μW is required for stable trapping, which is significantly decreased compared to previous PC cavity designs [39][40][41]53].…”
Section: Introductionmentioning
confidence: 94%
“…So far, via optical trapping, a large number of different nanoparticles including dielectric/metallic nanoparticles, single cells, and even single atoms can be manipulated [8][9][10]. Particularly, to further establish trapping nanoparticles with lower input powers, a number of new, near-field optical manipulation techniques, such as optical nanofibers [11][12][13], photonic crystal (PC) fibers [14,15], whispering gallery mode carousels [16][17][18][19][20], plasmonic tweezers [21][22][23][24], solid waveguides [25,26], slot waveguides [27,28], microring resonators [29], photonic crystal waveguides [30][31][32], and photonic crystal cavities [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], have been developed to exploit the strong spatial field gradient forces and to increase the field amplitude inside the devices. Among these, photonic crystal cavities have been investigated as advantageous platforms for cavity-enhanced optical trapping and sensing due to their a...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, by analyzing the intensity of light scattered by a trapped particle, they quantified the interaction force between the resonator surface and a 100 nm trapped particle with sub‐pN resolution—a technique they named nanophotonic force microscopy (NFM) . Two‐dimensional photonic crystal optical traps have also been reported for precisely measuring the size distribution of sub‐100 nm gold nanoparticles, and trapping and analyzing larger dielectric particles ( d > 0.25 µm) and bacteria at sub‐mW powers . These latter devices hold potential for applications in bacteria sensing or analysis.…”
Section: Fixed‐position Trapsmentioning
confidence: 99%
“…66 Two-dimensional photonic crystal optical traps have also been reported for precisely measuring the size distribution of sub-100 nm gold nanoparticles, 67 and trapping and analyzing larger dielectric particles (d > 0.25 μm) and bacteria at sub-mW powers. [68][69][70][71][72][73] These latter devices hold potential for applications in bacteria sensing or analysis. Additionally, Renaut et al demonstrated rotational orientation control for a pair of adjacent 1 μm microspheres trapped on a photonic crystal, 74 indicating short-range nanomanipulation may also be achieved with photonic crystal optical traps.…”
Section: Photonic Crystal Trapsmentioning
confidence: 99%